Otoritas Jasa Keuangan Dalam Sistem Ketatanegaraan Indonesia: The Financial Services Authority in the Indonesian State System - Chika Ramadea; Ferry Edward (Faculty of Law, Universitas Trisakti, 2025)
Financial institutions with ownership links across various financial subsectors (conglomerates) have increased the complexity of transactions and interactions among financial institutions within the financial system. One of the new independent state institutions introduced is the Financial Services Authority (OJK). The main issues raised are whether the OJK has been independent in carrying out its duties and authority in accordance with Law No. 21 of 2011, and what is the position of the OJK in Indonesia's state structure? The method used in this is a normative research type with a descriptive research nature, supported by secondary data sourced from primary, secondary, and tertiary legal materials. The result and the concluded that the independence of the Financial Services Authority (OJK) is not fully pure, as it is bound by laws, regulations, and external oversight bodies such as the Financial Audit Agency (BPK) and the People’s Representative Council (DPR). Furthermore, the OJK is an auxiliary state institution that plays a role in overseeing and evaluating its performance and policies to ensure transparency, accountability, and prevent abuse of power, while maintaining a balance of power.